2001
DOI: 10.1159/000048757
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Sex Steroids on T and B Cells: Modulation of Cell Cycle Phase Distribution, Apoptosis and bcl-2 Protein Levels

Abstract: Sex steroids have dramatic and differential effects on classic endocrine organ proliferation and apoptosis. In this investigation we sought to delineate similar effects of sex steroids on proliferation, cell cycle phase and apoptosis in lymphocyte cell lines as models for T and B cells. Estrogen and testosterone inhibited T cell line proliferation, induced accumulation of cells in S/G2M phases of the cell cycle, and increased apoptosis in a concentration- and time-dependent manner. There was a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 47 publications
(64 reference statements)
3
78
0
2
Order By: Relevance
“…The decreased lymphocyte counts in males as compared to females may be due to the increased testosterone concentrations, since testosterone may increase apoptosis in T cells 24 . Also studies in animals have shown an effect of estrogens on B cell development: estrogens increase bone marrow progenitor B cells in mice by protecting the progenitor cells from apoptosis 25 .…”
Section: Comparison Of All the Phase Of Women With Menmentioning
confidence: 99%
“…The decreased lymphocyte counts in males as compared to females may be due to the increased testosterone concentrations, since testosterone may increase apoptosis in T cells 24 . Also studies in animals have shown an effect of estrogens on B cell development: estrogens increase bone marrow progenitor B cells in mice by protecting the progenitor cells from apoptosis 25 .…”
Section: Comparison Of All the Phase Of Women With Menmentioning
confidence: 99%
“…Cell cycle analysis was performed as previously described [38,39]. Briefly, 1×10 6 were grown in suspension, harvested by centrifugation, washed, and fixed in 1% paraformaldehyde.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…For Western analysis, 2 to 5×10 6 cells were cultured (1.0×10 6 /ml) and stimulated bcl-2 and p53 protein levels were assayed as previously described [38,39]. All antibodies were diluted in 1 % milk in TBS.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations